Mary as Mother in the Flores de Mayo in Poblacion, Oslob - Patricia Marion Y. Lopez (Humanities Diliman, 2016)
The paper reflects on the meanings of the Flores de Mayo ritual as performed in a town on the southeastern coast of Cebu through the examination of Mary as a “semantically open” symbol. The essay illustrates how ideas about Mary are constructed through the discourse of the Church and are in turn, reinforced through a Church-instituted and regulated ritual. An analysis of selected elements of the ritual however, reveals that the symbol of Mary has the potential to hold “other” kinds of meanings that slip in between “official” and “unofficial” discourses, highlighting how Mary continues to be a negotiated field between church authorities and the popular faithful.